Examine the Effect of the Environmental and Social Disclosures on Profitability: Evidence from the Turkish Banking Sector - FENEIR, ImadeMohamed (Finance and Business Economies Review, 2023)
This study sought to examine the impact of environmental and social disclosure practices on financial performance and firm profitability. Data was collected from the annual statements and financial reports of twelve commercial banks listed in Bursa Istanbul. Profitability variables were determined through return on assets, return on equity, and earnings per share, concerning environmental and social disclosure information, it was measured according to GRI. Accordingly, correlation testing and regression analysis were used to identify the relationship and impact of environmental and social disclosure at the end of 2019 on the profitability of banks at the end of 2020. The results of the study indicated that there was not a significant relationship or effect of environmental and social disclosure on profitability in commercial banks listed on the Bursa Istanbul. Thus, the alteration in profitability cannot be predicted by the change in the level of environmental and social disclosure. Regarding the level of disclosure in general is good and acceptable, as it reaches the level of 58% and an average of 30% for social disclosure and a level of 60% and an average of 26% for environmental disclosure